Unlocking the Potential of Vanadium Oxide for Ultrafast and Stable Zn2+ Storage Through Optimized Stress Distribution: From Engineering Simulation to Elaborate Structure Design. Issue 12 (25th October 2022) - Gao, Yuan; Xia, Linghan; Yin, Junyi; Gan, Zihan; Feng, Xiang; Meng, Guodong; Cheng, Yonghong; Xu, Xin
Abstract: Compared with lithium‐ion batteries (LIBs), aqueous zinc batteries (AZIBs) have received extensive attention due to their safety and cost advantages in recent years. The cathode determines the electrochemical performance of AZIBs to a large extent. Vanadium‐based materials exhibit excellent capacity when used as AZIB cathodes. However, unexpected structural stress is inevitably induced during cycling and high current densities, which can gradually lead to structural deterioration and capacity decay. In fact, the stress/strain distribution in nanomaterials is crucial for electrochemical performance. In this work, the optimized stress distribution of the hierarchical hollow structure is verified by the finite element simulation of COMSOL software firstly. Guided by this model, a simple solvothermal method to synthesize hierarchical hollow vanadium oxide nanospheres (VO‐NSs), consisting of ≈10 nm ultrathin nanosheets and ≈500 nm hollow inner cavities, is employed. And a highly disordered structure is introduced to the VO‐NSs by in situ electrochemical oxidation, which can also weaken the structural stress during Zn 2+ insertion and extraction. Benefiting from this unique structure, VO‐NSs exhibit high‐rate and stable Zn 2+ storage capability. The strategy of engineering‐driven material design provides new insights into the development of AZIB cathodes. Abstract : The optimized stress distribution in a hierarchical hollow structure is verified by COMSOL finite element simulation firstly. Guided by this model, uniform hierarchical hollow nanospheres with a size of ≈1 µm are prepared and an amorphous structure is introduced via in situ electrochemical oxidation, enabling high‐rate and stable Zn 2+ storage.